Analysis Student Mistake of Teacher Professional Education In Completing Story Problems Based on Newman Procedures - Reni Dwi Susanti; Marhan Taufik (International Journal of Trends in Mathematics Education Research, 2019)
The purpose of this study was to see students mistakes in solving story problems based on the Newman’s procedure. The type of research used is descriptive qualitative research. The data retrieval technique is done through observation and testing. The results showed that the error in the skills process was 33% and the lowest error in the answer error was 8.2%. Errors caused by students who cannot read symbols, charts or charts, cannot solve problems properly, are wrong in solving steps and cannot be published or explained properly.